1988
DOI: 10.1177/0095327x8801400207
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Success Rates In Simulated Combat: Intelligent Tactics vs. Force

Abstract: Bakan categorized military tactics according to their reliance on "force" or "intelligence" suggesting that tactics that rely on the latter are more effective. Intelligence refers to an emphasis on local creativity, surprise, stealth, and adaption, while force relates to an emphasis on central direction, direct power, and hierarchical structure. Bakan's hypothesis was tested in realistic field exercises (n = 237) that employed tactical engagement simulation of weapons to simulate casualties and record events. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The TES field training research demonstrated that the value of added training time or repeated practice for engagement skills greatly increased the odds of winning offensive battles (Hart & Sulzen, 1988;Sulzen, 1987;Sulzen, Whitmarsh, & Hart, 1989).…”
Section: Tactical Training Supportmentioning
confidence: 99%
“…The TES field training research demonstrated that the value of added training time or repeated practice for engagement skills greatly increased the odds of winning offensive battles (Hart & Sulzen, 1988;Sulzen, 1987;Sulzen, Whitmarsh, & Hart, 1989).…”
Section: Tactical Training Supportmentioning
confidence: 99%
“…Paper presented at the meeting of the American Psychological Association, Atlanta, GA. Sulzen, R.H. (1988). Development of observer/controller (O/C) guidebooks.…”
Section: Manprintmentioning
confidence: 99%